PENGARUH PENGAWASAN DAN PENGHARGAAN TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) GURU PAUD DI KABUPATEN MANOKWARI - Neti Karnati; Sari Murti Widihartati (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2018)
Organization Citizenship Behavior is an individual behavior which is not compulsory, explicity recognized by the reward system and very contributive to the effectiveness an efficiency of the fuction of organization.The Objektive of this research is to know effect of Control and Reward to the Organizational Citizenship Behavior (OCB) of eraly children non formal teachers in Kabupaten Manokwari. This research be expected can give a better eraly children non formal education contributionin real at Manokwari.The method used in this research is the survey method using a quantitative approach, and explain the causal relationship with path analysis.Data were collected by quesioner. The target population of the research amaounted to 133 early children non formal teachers in Kabupaten Manokwari. In this research The results result of research indicates:1)There is a positive direct effect of control to ocb, 2) There is a positive direct effect of reward to ocb, 3) There is a positive direct effcet control and reward to ocb.